Ant-based self-healing routing for enhancing lifetime of wireless sensor networks. (2018) - Lakshmi, Chaganti B.N.; Rao, S. Krishna Mohan
In self-healing routing (SHR), receivers autonomously decide whether to forward the packet using only knowledge of their hop distances of the destination but neither energy estimation nor residual battery power is analysed. Hence, failure may occur on the intermediate nodes causing the data loss in transmission. To overcome the disadvantages of SHR and enhance the lifetime of WSN, self-healing routing using ant colony optimisation (ACO) is proposed. In our proposed solution, the RREQ and RREP procedures are executed by the forward ant (FANT) and backward ant (BANT) respectively using ACO technique. Source node broadcast a FANT to the neighbouring nodes along the destination which collects the hop distance and residual energy of each node. The next hop is selected based on the probability of pheromone. On reaching the destination, a BANT is transmitted through the reverse path. The collected hop distance and residual energy of each node by the BANT is analysed at the source. By simulation results, we show that the ant-based self-healing routing reduces the delay and energy consumption while increasing the packet delivery ratio.